The Effect of Snowball Throwing Learning Model towards Integrated Thematic Learning Outcomes in Science Class V Students at SDN 104/II Sungai Pinang - Antik Estika Hader; Dwi Novri Asmara; Nurwasilah Nurwasilah (The Future of Education Journal, 2023)
Science learning is one of the lessons that has a very strategic and important role, especially in terms of improving the quality of human resources (Human Resources). continuously growing at a faster rate. Science learning carried out in elementary schools should be carried out by presenting a method or learning model that is not monotonous and more diverse so that it can make students feel more interested in taking part in learning, besides that science learning should make students feel actively involved both physically and mentally. nor emotional. From the results of the observations, several problems were found in class V SDN 104/II Sungai Pinang, namely in class VA students who did not complete as much as 60% of the total students or a number of 18 students out of 23 students (KKM score 75), and class VB who completed as much as 70% of the total students or a number of 15 students from 22 students. This shows that more than 50% of students in the class, both VA and VB classes, still have not mastered the learning provided well enough, for this reason the teacher is obliged to carry out various kinds of efforts in order to improve the learning outcomes of his students in class. One of them is that it can be done by choosing a model, strategy or learning method that is considered appropriate, so that later it is expected to be able to involve students both to be able to play a more active role both in terms of emotional, physical and social. The researcher tries to apply the Snowball Throwing learning model, the results of the hypothesis test at a significant level of 0.05 after applying the Snowball Throwing learning model are obtained sig <α (0.00 <0.05), thus meaning that the test results are not in the H0 acceptance area so that Ha , so that it can be concluded that the Snowball Throwing learning model has a significant influence on the integrated thematic learning outcomes of science content in fifth grade students at SDN 104/II Sungai Pinang